Verbalization of mentality by means of semantic structure of Russian adjectives - K V Akopyan (Russian journal of linguistics: Vestnik RUDN, 2011)
Article is devoted to the variation in the ways and means of formation of some lexical items, especially the Russian adjectives which are used for man's mental features designation.